CopenFast trial: Faster-acting insulin Fiasp versus insulin NovoRapid in the treatment of women with type 1 or type 2 diabetes during pregnancy and lactation - a randomised controlled trial - Peter Damm; Lene Ringholm; Tine Dalsgaard Clausen; Sidse Kjærhus Nørgaard; Elisabeth Reinhardt Mathiesen (BMJ Open)
Introduction Faster-acting insulin aspart (Fiasp) is approved for use in pregnancy and lactation, but no clinical study has evaluated its effects during this life stage in women with pre-existing diabetes. The aim of the CopenFast trial is to evaluate the effect of Fiasp compared with insulin aspart (NovoRapid) on maternal glycaemic control during pregnancy, delivery and lactation and on fetal growth and infant health.Methods and analysis An open-label randomised controlled trial of pregnant women with type 1 or type 2 diabetes including women on multiple daily injection (MDI) therapy or insulin pump therapy. During a 2-year inclusion period, approximately 220 women will be randomised 1:1 to Fiasp or NovoRapid in early pregnancy and followed until 3 months after delivery. At 9, 21 and 33 gestational weeks and during planned induction of labour or caesarean section, women are offered blinded continuous glucose monitoring (CGM) for 7 days. Randomisation will stratify for type of diabetes and insulin treatment modality (MDI or insulin pump therapy, respectively). Health status of the infants will be followed until 3 months of age. The primary outcome is birth weight SD score adjusted for gestational age and gender. Secondary outcomes include maternal glycaemic control including glycated haemoglobin, preprandial and postprandial self-monitored plasma glucose levels, episodes of mild and severe hypoglycaemia, maternal gestational weight gain and weight retention, CGM time spent in, above and below target ranges as well as pregnancy outcomes including pre-eclampsia, preterm delivery, perinatal mortality and neonatal morbidity. Data analysis will be performed according to the intention-to-treat principle.Ethics and dissemination The trial has been approved by the Regional Ethics Committee (H-19029966) on 7 August 2019. Results will be sought disseminated in peer-reviewed journals and at scientific meetings.Trial registration number NCT03770767